To Print or Not to Print Medical Textbooks: Is That the Question? - Barbara Amelia Nace (Issues in Science and Technology Librarianship, 2005)
Looks at the concept of publishing of medical textbooks. Overview of electronic publishing of medical textbooks; Difference between print and electronic publications; Outlook for the advent of electronic publishing.